2017
DOI: 10.2337/db17-0577
|View full text |Cite|
|
Sign up to set email alerts
|

Engineering Glucose Responsiveness Into Insulin

Abstract: Insulin has a narrow therapeutic index, reflected in a small margin between a dose that achieves good glycemic control and one that causes hypoglycemia. Once injected, the clearance of exogenous insulin is invariant regardless of blood glucose, aggravating the potential to cause hypoglycemia. We sought to create a "smart" insulin, one that can alter insulin clearance and hence insulin action in response to blood glucose, mitigating risk for hypoglycemia. The approach added saccharide units to insulin to create… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
95
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(102 citation statements)
references
References 19 publications
6
95
0
1
Order By: Relevance
“…The competition of MK‐2640 binding between the insulin receptor vs. to MRC1 is modulated by blood glucose concentration. The two trials that are presented in this report sought to evaluate safety and tolerability of MK‐2640 and test for clinical translation of the glucose‐responsive PK/PD observed preclinically . In preclinical studies, in addition to glucose‐responsive PK/PD, two limitations were observed, low insulin potency and a high CL by MRC1 .…”
Section: Discussionmentioning
confidence: 99%
“…The competition of MK‐2640 binding between the insulin receptor vs. to MRC1 is modulated by blood glucose concentration. The two trials that are presented in this report sought to evaluate safety and tolerability of MK‐2640 and test for clinical translation of the glucose‐responsive PK/PD observed preclinically . In preclinical studies, in addition to glucose‐responsive PK/PD, two limitations were observed, low insulin potency and a high CL by MRC1 .…”
Section: Discussionmentioning
confidence: 99%
“…One approach to creating a GRI is to synthesize insulin analogs that retain capacity to bind to the insulin receptor (IR) and additionally can bind to the mannose receptor (MR) (7)(8)(9)(10). Binding of this type of GRI to the MR is enabled by the attachment of saccharides to an insulin backbone; the result of such binding is that the GRI is delivered for lysosomal degradation.…”
mentioning
confidence: 99%
“…Binding of this type of GRI to the MR is enabled by the attachment of saccharides to an insulin backbone; the result of such binding is that the GRI is delivered for lysosomal degradation. With appropriate selection of saccharides, binding to the MR can be modulated by ambient levels of blood glucose, being greatest at low and normal glucose concentrations and correspondingly reduced with higher glycemic levels (7)(8)(9)(10). Thus, clearance of the GRI will be higher at low ambient glucose, lowering its availability for IR binding and insulin action.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, tremendous efforts have been devoted to the development of smart insulin delivery systems that mimic the glucose-dependent dynamic insulin secretion of β-cells, thereby reducing hyperglycemic condition and mitigating the risk of insulin-induced hypoglycemia associated with a miscalculated exogenous insulin dose (6,7). To this end, chemically driven synthetic closed-loop insulin delivery systems integrating phenylboronic acid (7)(8)(9)(10)(11)(12)(13)(14)(15)(16), glucose-binding protein (17)(18)(19)(20), and glucose oxidase (21)(22)(23)(24)(25)(26) have been extensively studied. However, synthetic strategies to tightly regulate blood glucose levels with a low risk of hypoglycemia remain elusive in clinical practice (27).…”
mentioning
confidence: 99%